2020
DOI: 10.1007/s00383-020-04647-7
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized surgery of abdominal wall defects in Germany

Abstract: Purpose Neonatal surgery for abdominal wall defects is not performed in a centralized manner in Germany. The aim of this study was to investigate whether treatment for abdominal wall defects in Germany is equally effective compared to international results despite the decentralized care. Methods All newborn patients who were clients of the major statutory health insurance company in Germany between 2009 and 2013 and who had a diagnosis of gastroschisis or omphalocele were included. Mortality during the first y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
6
17
0
Order By: Relevance
“…Schmedding et al reported similar results with 82 % of gastroschisis as simple and mainly associated anomalies in omphalocele were trisomies (18 and 21), cardiac anomalies, and urinary tract anomalies. [18] Our non-GI anomaly rate in gastroschisis was similar to that reported by Payne et al [15,19] [16,19] We, however, have mostly term neonates in our series. We had 5 preterm neonates in our study including 4 with gastroschisis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Schmedding et al reported similar results with 82 % of gastroschisis as simple and mainly associated anomalies in omphalocele were trisomies (18 and 21), cardiac anomalies, and urinary tract anomalies. [18] Our non-GI anomaly rate in gastroschisis was similar to that reported by Payne et al [15,19] [16,19] We, however, have mostly term neonates in our series. We had 5 preterm neonates in our study including 4 with gastroschisis.…”
Section: Discussionsupporting
confidence: 88%
“…There was a huge difference in our mortality rates as compared to various other studies. [15][16][17][18][19][20][21][22][23][24] These differences might be due to various demographic and environmental factors in middle-income countries like India. Wright et al emphasized the role of surgical intervention in the survival of gastroschisis and documented a high mortality rate with contrasting statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroschisis is typically accompanied by intestinal non-rotation and may be associated with intestinal atresia and/or perforations. In contrast to omphalocele, gastroschisis is rarely associated with other congenital or chromosomal anomalies [ 11 ]. As the midgut is freely floating in the amniotic fluid, the intestine is typically thickened, edematous and foreshortened [ 12 ].…”
Section: Gastroschisismentioning
confidence: 99%
“…Complex (as compared to simple) gastroschisis occurs in about 11–28% of cases and is defined by the presence of intestinal complications including atresia, perforation or necrosis. Intestinal atresia is the most common anomaly associated with gastroschisis occurring in about 10–15% of patients [ 11 , 12 , 13 , 14 ].…”
Section: Gastroschisismentioning
confidence: 99%
“…Insurance companies increasingly evaluate their routine patient data, especially with respect to diagnoses, procedures, mortality and length of hospital stay. These datasets have been successfully used for epidemiological research [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%